2007
DOI: 10.1111/j.1464-0597.2007.00281.x
|View full text |Cite
|
Sign up to set email alerts
|

Counseling Psychology in France: A Paradoxical Situation

Abstract: Quelles sont les spécificités de la situation française concernant le counseling? Après avoir évoqué les termes utilisés en France, pour qualifier ces pratiques et leur origine, les auteurs exposent une situation qualifiée de paradoxale tant sur le plan des professionnels impliqués dans le counseling que de la recherche. En effet, alors que les besoins en accompagnement sont nombreux et croissants, les professionnels oeuvrant dans le champ du counseling présentent des pratiques très diversifiées et des profils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 24 publications
0
5
0
2
Order By: Relevance
“…Indeed, research has found that counselors are subject to psychosocial risks (e.g., burnout: Thompson, Amatea, & Thompson, 2014 ; workaholism: Machado, Desrumaux, & Dose, 2015 ). Counselors in particular may have work-related health problems because of work schedules and fragmented activities ( Bernaud et al, 2007 ). Other studies (e.g., Dose, Desrumaux, Sovet, & De Bosscher, 2018 showed that counselors can have a sense of well-being when their work conditions are good (i.e., objective career success, recognition of the hierarchy).…”
Section: Well-being and Leader-member Exchangementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, research has found that counselors are subject to psychosocial risks (e.g., burnout: Thompson, Amatea, & Thompson, 2014 ; workaholism: Machado, Desrumaux, & Dose, 2015 ). Counselors in particular may have work-related health problems because of work schedules and fragmented activities ( Bernaud et al, 2007 ). Other studies (e.g., Dose, Desrumaux, Sovet, & De Bosscher, 2018 showed that counselors can have a sense of well-being when their work conditions are good (i.e., objective career success, recognition of the hierarchy).…”
Section: Well-being and Leader-member Exchangementioning
confidence: 99%
“…By examining need satisfaction as a possible mediator between self-esteem and leader-member exchange (LMX), the predictors, and well-being, the criterion measure, our contributions to the literature are threefold. First, the literature is rather scarce concerning counselors’ health problems ( Bernaud, Cohen-Scali, & Guichard, 2007 ), and we do not know if their job can satisfy their psychological needs. Second, with few exceptions, the mediating effects of psychological needs and their links to self-esteem and well-being have not been studied much in regard to careers, vocational guidance, and counselors.…”
mentioning
confidence: 99%
“…In Hong Kong, counseling is viewed as an intervention strategy grounded in psychology yet shared by mental health and educational professionals. In France, some view counseling psychology as a peripheral approach to treating personal difficulties (Bernaud, Cohen‐Scali, & Guichard, this issue). In short, many mental health specialists view counseling as a process used by clinical, organisation, and school psychologists, and by social workers.…”
Section: Crystallise a Cross‐national Professional Identitymentioning
confidence: 99%
“…For example, they may suffer from compassion fatigue and burnout (Thompson, Amatea, & Thompson, ) or workaholism (Machado, Desrumaux, & Dose, ). Counselors in particular may have work‐related health problems because of work schedules and fragmented activities (Bernaud, Cohen‐Scali, & Guichard, ). We included French psychologists in our study in order to understand factors, such as POS, that might protect their job and that might be sources of accomplishment and success, whether psychological, hierarchical, or financial.…”
mentioning
confidence: 99%